Feedback Kinetics in Mechanochemistry: The Importance of Cohesive States. (30th October 2017) - Hutchings, Benjamin P.; Crawford, Deborah E.; Gao, Lei; Hu, Peijun; James, Stuart L.
Abstract: Although mechanochemical synthesis is becoming more widely applied and even commercialised, greater basic understanding is needed if the field is to progress on less of a trial‐and‐error basis. We report that a mechanochemical reaction in a ball mill exhibits unusual sigmoidal feedback kinetics that differ dramatically from the simple first‐order kinetics for the same reaction in solution. An induction period is followed by a rapid increase in reaction rate before the rate decreases again as the reaction goes to completion. The origin of these unusual kinetics is found to be a feedback cycle involving both chemical and mechanical factors. During the reaction the physical form of the reaction mixture changes from a powder to a cohesive rubber‐like state, and this results in the observed reaction rate increase. The study reveals that non‐obvious and dynamic rheological changes in the reaction mixture must be appreciated to understand how mechanochemical reactions progress.